Extraterritorial U.S. sanctions: Only domestic courts could effectively curb the enforcement of U.S. law abroad - Sascha Lohmann (Stiftung Wissenschaft und Politik (SWP), 2019)
The long reach of U.S. law affects persons, property, and acts around the world. In trying to shield EU-based individuals and entities with commercial interests from its adverse impact, European policy-makers have recently been exposed as more or less helpless. In order to pursue their strategic objectives more effectively, Europeans must not only focus on increasing strategic autonomy vis-à-vis the U.S. government. Absent a diplomatic agreement with the executive branch, they must also better utilize available channels of influence. One potential avenue would be to substantially support EU-based companies in domestic courts - both diplomatically as well as financially - in order to challenge the executive branch when enforcing U.S. law beyond borders. Only the judicial branch can effectively curb the extraterritorial application of U.S. jurisdiction.
Keywords: 320